Stress-Activated Protein Kinases in Human Fungal Pathogens - Day, Alison M.; Quinn, Janet (Frontiers in Cellular and Infection Microbiology, 2019)
The ability of fungal pathogens to survive hostile environments within the host depends on rapid and robust stress responses. Stress-activated protein kinase (SAPK) pathways are conserved MAPK signaling modules that promote stress adaptation in all eukaryotic cells, including pathogenic fungi. Activation of the SAPK occurs via the dual phosphorylation of conserved threonine and tyrosine residues within a TGY motif located in the catalytic domain. This induces the activation and nuclear accumulation of the kinase and the phosphorylation of diverse substrates, thus eliciting appropriate cellular responses. The Hog1 SAPK has been extensively characterized in the model yeast Saccharomyces cerevisiae. Here, we use this a platform from which to compare SAPK signaling mechanisms in three major fungal pathogens of humans, Candida albicans, Aspergillus fumigatus, and Cryptococcus neoformans. Despite the conservation of SAPK pathways within these pathogenic fungi, evidence is emerging that their role and regulation has significantly diverged. However, consistent with stress adaptation being a common virulence trait, SAPK pathways are important pathogenicity determinants in all these major human pathogens. Thus, the development of drugs which target fungal SAPKs has the exciting potential to generate broad-acting antifungal treatments.